AODTU-007 Mertk expressing hepatic macrophages promote the resolution of inflammation in acute liver failure. (17th June 2017) - Triantafyllou, E; Pop, O; Possamai, L; Wilhelm, A; Liaskou, E; Petts, G; Singanayagam, A; Bernsmeier, C; Khamri, W; Patel, V; Stamataki, Z; Curbishley, S; et al.
Abstract : Introduction: Acute liver failure (ALF) is characterised by overwhelming hepatocyte death and liver inflammation with massive infiltration of myeloid cells in necrotic areas. The mechanisms underlying resolution of acute hepatic inflammation are largely unknown. Here, we aimed to investigate the impact of Mer-Tyrosine-Kinase (MerTK) during ALF and also examine how the micro-environmental mediator, Secretory Leukocyte Protease Inhibitor (SLPI), governs this response. Method: Flow cytometry, immunohistochemistry and confocal imaging determined the phenotype, functional profile and tissue topography of MerTK+ monocytes/macrophages in human ALF, healthy and disease controls. The temporal evolution of macrophage MerTK expression and its impact on resolution was examined in APAP-induced acute liver injury using WT and Mer −/− mice. SLPI effects on hepatic myeloid cells were determined in vitro and in vivo using APAP-treated WT mice. Results: We demonstrate an expansion of prorestorative MerTK+HLA-DR high cells in circulatory/tissue compartments of ALF patients (Fig.A). Compared to WT mice which have an increase of MerTK+MHCII high macrophages during the resolution phase in ALF (Fig.B), APAP-treated Mer −/− mice exhibit persistent liver injury and inflammation, characterised by a decreased proportion of resident Kupffer cells (KC) and increased number of neutrophils (Fig.C). Both in vitro and in APAP-treated mice (Fig.D), SLPI reprograms macrophages towards resolution responses through induction of a MerTK+HLA-DR high phenotype that promotes neutrophil apoptosis and their subsequent clearance. Conclusion: We identify a hepatoprotective, MerTK+, macrophage phenotype that evolves during the resolution phase following ALF and represents a novel immunotherapeutic target to promote resolution responses following acute liver injury. Disclosure of Interest: None Declared